Character Education in Shaping a Disciplined and Noble Generation: A Study of Children Aged 4-6 Years at RA Perwanida Brawijaya - Arin, Arini Mubaroroh; Sa'dun Akbar (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study aims to uncover the implementation of character education for children aged 4-6 years at RA Perwanida Brawijaya, Pamekasan. The method used is a qualitative approach with descriptive data collection, using the principal and teachers of RA Perwanida Brawijaya as primary data sources, and literature from books and the internet as secondary data. The research findings indicate that character education at RA Perwanida Brawijaya, Pamekasan, is implemented through routine activities, incidental activities, and the "Blessed Friday Charity" program that assist in the development of empathy, care for others, and understanding the significance of giving in Islam. The limitations of this study lie in the implementation of character education at RA Perwanida Brawijaya, Pamekasan. The execution of character education can help children face life's challenges and enhance their future quality of life through the formation of positive attitudes. This character education implementation through routine activities, incidental activities, and school programs allows children to develop good character traits consistent with the values and beliefs instilled in the educational process, becoming an integral part of their personality.